Hexagonal layered group IV–VI semiconductors and derivatives: fresh blood of the 2D family. Issue 25 (17th June 2020) - Tian, Xiao-Qing; Duan, Jing-Yi; Kiani, Maryam; Wei, Ya-Dong; Feng, Naixing; Gong, Zhi-Rui; Wang, Xiang-Rong; Du, Yu; Yakobson, Boris I.
Abstract : New phases of group IV–VI semiconductors in 2D hexagonal structures are predicted and their unusual physical properties are revealed. Abstract : New phases of group IV–VI semiconductors in 2D hexagonal structures are predicted and their unusual physical properties are revealed. The structures of monolayer group IV–VI semiconductors are similar to those of blue phosphorene and each unit has the same ten valence electrons. The band gap of 2D hexagonal group IV–VI semiconductors depends on both the thickness and stacking order. Atomic functionalization can induce ferromagnetism, and the Curie temperature can be tuned. Gapped Dirac fermions with zero mass are developed and this makes it exceed that of graphene. The Fermi velocity can be compared to or even above that of graphene.